2017
DOI: 10.5194/acp-17-5063-2017
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of black carbon, brown carbon, and absorption enhancement from clear coatings in biomass burning emissions

Abstract: Abstract. A wide range of globally significant biomass fuels were burned during the fourth Fire Lab at Missoula Experiment (FLAME-4). A multi-channel photoacoustic absorption spectrometer (PAS) measured dry absorption at 405, 532, and 660 nm and thermally denuded (250 • C) absorption at 405 and 660 nm. Absorption coefficients were broken into contributions from black carbon (BC), brown carbon (BrC), and lensing following three different methodologies, with one extreme being a method that assumes the thermal de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
96
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 66 publications
10
96
1
1
Order By: Relevance
“…From prescribed burns conducted in boreal forests (northern Ontario, Canada), Mazurek et al (1991) reported a range of 10-18 and 21-95 for full-flaming and smoldering fire conditions, respectively. A chamber experiment conducted with typical Siberian biomass (pine) showed that the OC / EC ratios for PM 10 in fresh (aged) smoke for flaming and smoldering are 0.3 (2.3) and 181 (126), respectively (Popovicheva et al, 2015). In addition, the OC / EC ratios for fresh forest debris smoke were found to be 0.6 and 35 in flaming and smoldering fires, respectively.…”
Section: Characterisation Of Polluted Airmentioning
confidence: 99%
See 1 more Smart Citation
“…From prescribed burns conducted in boreal forests (northern Ontario, Canada), Mazurek et al (1991) reported a range of 10-18 and 21-95 for full-flaming and smoldering fire conditions, respectively. A chamber experiment conducted with typical Siberian biomass (pine) showed that the OC / EC ratios for PM 10 in fresh (aged) smoke for flaming and smoldering are 0.3 (2.3) and 181 (126), respectively (Popovicheva et al, 2015). In addition, the OC / EC ratios for fresh forest debris smoke were found to be 0.6 and 35 in flaming and smoldering fires, respectively.…”
Section: Characterisation Of Polluted Airmentioning
confidence: 99%
“…In addition, due to the lensing effect, organic coatings can substantially modify the optical properties of EC in mixed particles. Thus, laboratory experiments have shown that the light absorption enhancement factor for internal mixtures of EC with organic and inorganic coatings can range from 1.3 to 3.5 (Schnaiter et al, 2005;Mikhailov et al, 2006;Zhang et al, 2008;Shiraiwa et al, 2010;Pokhrel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous modeling studies have typically used either the lower or higher bound from laboratory studies to estimate the minimum or maximum absorption properties of BrC (Feng et al, 2013;Lin et al, 2014). In addition, it is unclear what fraction of the OA is BrC and how this differs with source and ambient combustion conditions (Pokhrel et al, 2017). In laboratory studies organics are not always fully soluble; typically, 40-90 % of the total material can be extracted, depending on the solvent (e.g., ∼ 40 % can be extracted in water and more than 90 % can be extracted in methanol; Chen and Bond, 2010).…”
mentioning
confidence: 99%
“…Thus, the B abs contribution from BC at 401 nm can be calculated from 2.17 times B abs at 870, and any additional B abs at 401 can be assigned to BrC subject to limitations due to "lensing" by coatings discussed elsewhere (Pokhrel et al, 2016;Lack and Langridge (2013)). Pokhrel et al (2017) found that coatings typically accounted for much less than 30% of absorption in room burn smoke 1-2 hours old and coatings are likely much less important in 5 s old stack burn smoke (Akagi et al, 2012).…”
mentioning
confidence: 99%
“…Coating effects are very difficult to deconvolve from BrC effects even with additional instruments that were not available during 20 the stack burns (Pokhrel et al, 2017). This adds some uncertainty to the BrC attribution, but not to the absorption measurements themselves.…”
mentioning
confidence: 99%